PERUBAHAN TUTUPAN LAHAN DAN LINGKUNGAN: AKUNTING SUMBERDAYA ALAM PROPINSI KALIMANTAN SELATAN - Rony M. Bishry (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
The natural resources utilization for economic development has became the driver of land cover and and environmental change. The policy of natural resources utilization for development in Kalimantan Selatan has changed the net value of its natural resource capital. For Kalimantan Selatan Province it is recorded that between the year of 2004 - 2007, the economic value of its natural resources has changed as much as Rp. 621,9 billion. However comparing to the need of annual budget to treat the critical land amounting to Rp 555,9 billion and the depreciation of its roads amounting to the Rp. 1 Trillion, the net value of its natural resources capital is relatively small. Key Word: natural resources and environment, regional developmentKey Word: natural resources and environment, regional development